Long-term outcomes of standardized training for caregivers of children with tracheostomies: The IStanbul PAediatric Tracheostomy (ISPAT) project - ERGENEKON, ALMALA PINAR; GÖKDEMİR, YASEMİN; KARADAĞ, BÜLENT TANER (My University, 2023)
Background and Objectives: Children with tracheostomies are at increased risk of tracheostomy-related complications and require extra care. Standardized training programs for caregivers can improve tracheostomy care and reduce complications. In this study, we compared caregiver knowledge and skill scores after a standardized theoretical and practical training program on tracheostomy care (IStanbul PAediatric Tracheostomy (ISPAT) project) immediately and 1 year post-training and evaluated how this training affected the children\"s clinical outcomes. Materials and Methods: We included 32 caregivers (31 children) who had received standardized training a year ago and administered the same theoretical and practical tests 1 year after training completion. We recorded tracheostomy-related complications and the number and reasons for admission to the healthcare centers. All data just before the training and 1 year after training completion were compared. Results: After 1 year of training completion, the median number of correct answers on the theoretical test increased to 16.5 from 12 at pretest (p < 0.001). Compared with pretest, at 1-year post-training practical skills assessment scores, including cannula exchange and aspiration, were significantly higher (both p < 0.001) and mucus plug, bleeding, and stoma infection reduced significantly (p = 0.002, 0.022, and 0.004, respectively). Hands-on-training scores were better than pretest but declined slightly at 1 year compared to testing immediately after training. Emergency admission decreased from 64.5% to 32.3% (p = 0.013). Hospitalization decreased from 61.3% to 35.5% (p = 0.039). Conclusion: Our findings indicate that caregiver training can lead to a persistent increase in knowledge and skill for as long as 1 year, as well as improvements in several measurable outcomes, although a slight decrease in scores warrants annual repetitions of the training program.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Göğüs Hastalıkları ve Allerji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Chest Diseases and Allergy; Health Sciences; Klinik Tıp (MED); Klinik Tıp; SOLUNUM SİSTEMİ; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; RESPIRATORY SYSTEM; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Akciğer ve Solunum Tıbbı; Pediatrics, Perinatology and Child Health; Pulmonary and Respiratory Medicine; caregiver; long-term outcome; tracheostomy; training